2012
DOI: 10.1103/physrevlett.109.207001
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Spin-Polarized Quasiparticle Transport in Mesoscopic Al Superconductors with a Zeeman Splitting

Abstract: We report on nonlocal transport in multiterminal superconductor-ferromagnet structures, which were fabricated by means of e-beam lithography and shadow evaporation techniques. In the presence of a significant Zeeman splitting of the quasiparticle states, we find signatures of spin transport over distances of several μm, exceeding other length scales such as the coherence length, the normal-state spin-diffusion length, and the charge-imbalance length. The relaxation length of the spin signal shows a nearly line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 21 publications
8
129
0
Order By: Relevance
“…A well-known application beyond the linear regime are normal-metal/insulator/superconductor (NIS) junctions under voltage bias close to the energy gap of the superconductor, which provide local electronic refrigeration [1011]. Charge and spin transport in the nonlinear bias regime have also been investigated experimentally [89] and theoretically [1923]. …”
Section: Introductionmentioning
confidence: 99%
“…A well-known application beyond the linear regime are normal-metal/insulator/superconductor (NIS) junctions under voltage bias close to the energy gap of the superconductor, which provide local electronic refrigeration [1011]. Charge and spin transport in the nonlinear bias regime have also been investigated experimentally [89] and theoretically [1923]. …”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we summarize some of our recent experimental results on non-equilibrium charge and spin transport in nanoscale superconductors [12,1718], and perform additional numerical analysis to obtain more insight into the physical mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The combination between the spin and super-conducting (SC) transports is also expected to provide intriguing transport properties, leading to an emerging field in spintronics because a superconductor itself has great potential for future nanoelectronic applications such as Josephson circuit and quantum computing910. Although a number of experimental studies have been performed1112131415161718192021, several intriguing phenomena suggested in theoretical study have not been demonstrated222324. Moreover, the experimental study on subgap transports such as a crossed Andreev reflection and a spin triplet proximity effect have still exciting topics in superconducting spintronics because of their fantastic properties2526272829.…”
mentioning
confidence: 99%